Dexmedetomidine for prevention of early postoperative catheter-related bladder discomfort in voluntary kidney donors: Prospective, randomized, double-blind, placebo-controlled trial - Tapas Kumar Singh; Sandeep Sahu; Anil Agarwal; Devendra Gupta; Prabhaker Mishra (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Catheter-related bladder discomfort (CRBD) has started to gain recognition as a problem in early postoperative care. Dexmedetomidine reduces bladder contractility via M3 muscarinic receptor antagonism and α-2 receptor agonism, apart from its concomitant therapeutic benefits, such as sedation and sympatholysis, in a postoperative period. We, therefore, evaluated the efficacy of dexmedetomidine in reducing incidence and severity of CRBD. Material and Methods: This prospective, randomized, double-blind, placebo-controlled trial done on 110 voluntary kidney donors for live related kidney transplantations were planned for laparoscopic donor nephrectomy. The donors were of ages 18-60 years, American Society of Anesthesiologists physical status I and II of either sex. The control group received 20 ml normal saline (NS) intravenous (IV) infusion over 15 min, whereas the dexmedetomidine group received dexmedetomidine 1 μg/kg made in 20 ml NS as IV infusion over 15 min. The incidence and severity of CRBD were recorded as primary endpoints up to 12 h in early postoperative period. The incidence of bladder discomfort was analysed by Fisher's exact test and severity of bladder discomfort by Mann Whitney U test. Results: The incidence of CRBD on arrival at postoperative care unit was 18% in dexmedetomidine group compared to 42% in control group (P < 0.05). The incidence and severity of CRBD reduced in dexmedetomidine group at 0, 2, and 4 h compared with control group (P < 0.05). Conclusions: Dexmedetomidine 1 μg/kg administered IV to patients 30 min before extubation reduces the incidence and severity of CRBD in early postoperative settings with no adverse effects.